Engineering mechanics statics - Bedford, Anthony; Fowler, Wallace; Yusof Ahmad (Prentice Hall, 2008)
Engineering Mechanics: Statics in SI Units, provides students with a clear and thorough presentation of the theory and applications of this subject. By improving on the content, pedagogy, presentation and currency over the 12 editions, Hibbeler's Engineering Mechanics series is renowned for its clarity of explanation and robust problem sets; making it the best-selling course text for this subject.